Pengembangan Metode Pembelajaran PAI dengan Pendekatan ‎Teori Pemrosesan Imformasi dan Teori Neuroscience - Reti Suryani; Zuhriyah, Indah Aminatuz (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2023)
This study aims to examine students' thinking and describe students' way of thinking in receiving information and storing information and processing information in Islamic Religious Education subjects with Islamic Religious Education learning development methods. This research uses a qualitative approach. This research aims to assist educators in providing learning in the classroom to make it easier for educators to solve complex problems in PAI learning.